2018
DOI: 10.1002/admi.201801291
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Intermetallic Co3Sn2 and Ni3Sn2 Thin Films

Abstract: crystal structures of the participating metal components. An intermetallic compound is formed when the bonds between the dissimilar atoms are stronger than the bonds between the atoms of the same element.Because of their specific structure, intermetallic compounds usually exhibit unique physical and chemical properties that are potentially superior to their disordered alloy analogues and the pure metals. Such properties include, for example, magnetoresistance, [3,4] superconductivity, [5][6][7] enhanced cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…The selection of suitable reagents and processes makes ALD much more demanding than CVD and has been introduced for the synthesis of intermetallic compounds in 2016 for NiFe films [ 152 ]. Since then, it has been applied to synthesise PtSn/SiO2 [ 153 ], nanoparticles of PtIn [ 154 ] and PtSn [ 155 ] as well as thin films of Co 3 Sn 2 and Ni 3 Sn 2 [ 156 ].…”
Section: Developments In Synthesismentioning
confidence: 99%
“…The selection of suitable reagents and processes makes ALD much more demanding than CVD and has been introduced for the synthesis of intermetallic compounds in 2016 for NiFe films [ 152 ]. Since then, it has been applied to synthesise PtSn/SiO2 [ 153 ], nanoparticles of PtIn [ 154 ] and PtSn [ 155 ] as well as thin films of Co 3 Sn 2 and Ni 3 Sn 2 [ 156 ].…”
Section: Developments In Synthesismentioning
confidence: 99%
“…This direct film growth on non-metallic surfaces is in agreement with prior ALD studies by Väyrynen employing the same Co precursor for Co3Sn2 intermetallic films. 46 Contrasting this, the thermal ALD process developed by Kerrigan and co-workers with Co(DAD)2 was strongly inhibited on all surfaces except metallic ones. 11 This suggested that unlike Co(DAD)2, CoCl2(TMEDA) is capable of interacting with hydroxyl surface sites during the first pulse.…”
Section: Ald Process Developmentmentioning
confidence: 85%
“…43 To address this crucial drawback, we present for the first time the ALD of metallic, Zn-free Co thin films using, intramolecularly stabilized Zn precursor Zn(DMP)2 44 (DMP = N,N-3-(dimethylamino)propyl) with the Co precursor CoCl2(TMEDA) (TMEDA = N,N,N',N'-tetramethylethylenediamine) that has previously been used for ALD of intermetallic thin films. 45,46 The precursor pair was chosen based on the precedence for the formation of thermally labile Co(DMP)2 species in solution, 47 a bulk reactivity study with the neat reagents, as well as matching thermal properties that facilitate their usage in an F-120 ALD reactor. As a first step, a reactivity screening of several potential precursor combinations (see Scheme 1) comprising the wellknown Zn(Et)2 43 as well as its less known amine stabilized congener Zn(Et)2(TMEDA) 48 is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Other substrates, such as Si with native oxide, TiN, Cu, Au, and Ru, were also tested. NiCl 2 (TMPDA) was synthesized in‐house according to the procedure described previously . TBH was purchased from EpiValence and AlCl 3 from Acros Organics.…”
Section: Methodsmentioning
confidence: 99%
“…So far, no suitable reducing agent has been found to reduce CoCl 2 (TMEDA) or NiCl 2 (TMPDA) to elemental Co or Ni in ALD. We have, however, shown that the diamine adducts of these metal(II) halides are suitable for the ALD of intermetallic Co 3 Sn 2 and Ni 3 Sn 2 as well as Co(II) oxide thin films …”
Section: Introductionmentioning
confidence: 99%